Validity and Reliability of the Hockey Playing Tactics Assessment Instrument - Hidayat, Yudi; Hambali, Sumbara (STKIP Pasundan, 2025)
This research aims to develop and test the validity and reliability of an assessment instrument for hockey playing tactics in the context of student sports coaching. The research uses an instrument development design with a quantitative evaluative approach. The research subjects are members of the Hockey Student Activity Unit (UKM Hoki) at STKIP Pasundan, who are involved in modified games (small-sided games). Content validity is tested through expert judgment using Aiken’s V index, while construct validity is analyzed through item-total correlation. Instrument reliability is tested using Intraclass Correlation Coefficient (ICC) and Cronbach’s Alpha. The research results show that all instrument indicators have good content validity and construct validity, as well as high inter-rater reliability and internal consistency. Thus, the developed instrument is declared valid and reliable for assessing students' hockey playing tactic abilities, and is suitable for use in the context of sports coaching and learning in higher education.